Analysis of nutritional content and heavy metals of suckermouth catfish (Pterygoplichthys pardalis) in Lake Sidenreng, South Sulawesi, Indonesia - Hasrianti Hasrianti; Armayani M; Surianti Surianti; A Rini Sahni Putri; Abd Hakim Akbar (Society for Indonesian Biodiversity, 2022)
Abstract. Hasrianti, Armayani M, Surianti, Putri ARS, Akbar AH. 2022. Analysis of nutritional content and heavy metals of suckermouth catfish (Pterygoplichthys pardalis) in Lake Sidenreng, South Sulawesi, Indonesia. Biodiversitas 23: 3539-3545. Suckermouth catfish (Pterygoplichthys spp.) is one type of freshwater fish that belongs to the category of invasive fish (invasive alien species) in Indonesia based on the regulation of the Indonesian Minister of Marine Affairs and Fisheries Number PER.17/MEN/2009. The presence of suckermouth catfish in Lake Sidenreng with a high population level and increasing over time has resulted in this species dominating the waters. The many impacts caused and the solution has not been found to eradicate the fish, so we need an alternative that can be used to utilize suckermouth catfish, for example, as food to be processed into fishery products. In order to be used as raw material for processed food, a study is needed to determine the nutritional content and heavy metal content in suckermouth catfish. Based on the results of the analysis of the content of crude protein, crude fat and carbohydrate content in the meat of a large (40.3 cm), the content values were 14.52%, 0.49% and 0.21%, while the crude protein, crude fat and fat content were Carbohydrates contained in the meat of suckermouth catfish which are smaller in size (21 cm) are 14.58%, 0.52% and 0.09%. Heavy metals Pb, As, Cd and Hg contained in the meat and scales of suckermouth catfish are also below the metal contamination threshold required based on SNI 2729:2013 so that the fish can be categorized as fish fit for consumption and can be processed into various fishery products with economic value.